PENGARUH KEPUASAN KERJA DAN JOB INSECURITY TERHADAP TURNOVER INTENTION KARYAWAN OUTSOURCING PT X - Diyah Ayu Indarwati; Yudi Tri Harsono (Flourishing Journal, 2022)
Abstract This study aimed to determine the effect of job satisfaction and job insecurity on the turnover intention of PT. X’s outsourcing employees. This research hypothesis is that job satisfaction and job insecurity affect the turnover intention of outsourcing employees of PT X. The subjects of this study are 54 PT. X’s outsourcing employees. The data collection method used in this study is a questionnaire consisting of 3 scales, namely job satisfaction scale, job insecurity scale and turnover intention scale. The job satisfaction scale consists of 16 items constructed by the researcher based on the job satisfaction aspect proposed by Luthans et al. (2021), the job insecurity scale consists of 10 items constructed by the researcher based on the job insecurity aspect proposed by Rowntree (2005), and the turnover intention scale consists of 10 items constructed by the researcher based on the turnover intention aspect proposed by Mobley (2011). The result of the analysis of research data for hypothesis testing using multiple linear regression is that there is a simultaneous and significant effect of job satisfaction and job insecurity on the turnover intention of PT. X’s outsourcing employees of 56.2% with a significance value of (p) <0.05. Keywords: job satisfaction; job insecurity; turnover intention; outsourcing employee Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh kepuasan kerja dan job insecurity terhadap turnover intention karyawan outsourcing PT X. Hipotesis penelitian ini adalah terdapat pengaruh kepuasan kerja dan job insecurity terhadap turnover intention karyawan outsourcing PT X. Subjek penelitian ini adalah 54 karyawan outsourcing PT X. Metode pengambilan data pada penelitian ini menggunakan kuesioner yang terdiri dari 3 skala, yakni skala kepuasan kerja, skala job insecurity dan skala turnover intention. Skala kepuasan kerja terdiri dari 16 butir aitem yang dikonstruksikan oleh peneliti berdasarkan aspek kepuasan kerja yang dikemukakan oleh Luthans et al., (2021), skala job insecurity terdiri dari 10 butir aitem yang dikonstruksikan oleh peneliti berdasarkan aspek job insecurity yang dikemukakan oleh Rowntree (2005), dan skala turnover intention terdiri dari 10 butir aitem yang dikonstruksikan oleh peneliti berdasarkan aspek turnover intention yang dikemukakan oleh Mobley (2011). Analisis data penelitian untuk pengujian hipotesis menggunakan regresi linier berganda, hasilnya terdapat pengaruh simultan dan signifikan kepuasan kerja dan job insecurity terhadap turnover intention karyawan outsourcing PT X sebesar 56,2% dengan nilai signifikansi (p) < 0,05. Kata kunci: kepuasan kerja; job insecurity; turnover intention; karyawan outsourcing